A history of the Spanish lexicon a linguistic perspective - Dworkin, Steven Norman, 1947- (Oxford : Oxford University Press, 2012)
Written from the twin perspectives of linguistic and cultural change, this book describes the language inherited from Latin and how it was then influenced by the Visigothic and Arabic invasions, and later by contact with Old French, Old Provencal English and, not least, with the indigenous languages of South and Central America.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Spanish language -- History; Spanish language -- Lexicology, Historical